PEMFIGUS VULGARIS ORAL TERKAIT INFEKSI VIRUS HERPES SIMPLEKS (LAPORAN KASUS) - Surya Nelis (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEOral pemphigus vulgaris associated herpes simplex virus infection (case report)ABSTRACTPemphigus Vulgaris (PV) is an autoimmune mucocutaneous disease characterized by intraepithelial blister formation, which develops due to the interaction between predisposing genetic and environmental factors. Infections caused by members of the Herpesviridae family have been suggested as a possible triggering factor for PV. The purpose of this case report was to describe the case of a patient who has developed PV after showing herpetic infection, which refractory to corticosteroid therapy. A 49-year old-woman suffered from extensive multiple painful erosions/ulcers of the mouth. The lesions started on the buccal mucosa which subsequently involved the entired mouth. Histopathologic examination was suggestive of PV. The lesions developed concurrently with high titers of anti-HSV antibodies. These patient was treated with oral and topical corticosteroid, but showed incomplete remission. The titers of anti-HSV have followed the PV activity, reducing with the remission of the disease. Two months later, patient developed exacerbation of the lesions, following the return of high titers of anti-HSV IgG.The treatment with acyclovir has succeeded and all lesions have been completely healed. This case indicated that the lesions of PV which are refractory to corticosteroid therapy, should be considered to herpetic infection. Keywords : Oral pemphigus vulgaris, herpes simplex infection, autoimmune, corticosteroids